Metal Concentration In Water, Sediment, and Green Alga Halimeda opuntia (Linnaeus) J.V. Lamouroux from Totok Bay and Blongko Waters, North Sulawesi - . Nasprianto; Desy M.H. Mantiri; Grevo S Gerung (Sam Ratulangi University, 2019)
Heavy metals in the water and sediment, in spite of low concentration, will not degrade and even can be absorbed and biologically accumulated by marine algae. This study was aimed to analyze the heavy metal concentrations in the seawater, sediment, and Halimeda opuntia in Totok Bay and Blongko waters. Samples were analyzed using APHA method and USEPA method in Water Laboratory Nusantara (WLN). Results showed that the heavy metal concentration in Totok Bay waters was <0.0001 ppm for Cadmium (Cd), <0.001 ppm for lead (Pb), <0.005 ppm for Zinc (Zn), and <0.00005 ppm for mercury (Hg), respectively, while Blongko waters had Cd concentration of <0.0001 ppm, Pb <0.001 ppm, Zn <0,005 ppm, Hg <0.00005 ppm. Heavy metal concentration in the sediment of Totok Bay was 4.71 ppm for Cd, 10.7 ppm for lead, 58 ppm for Zn, and 2.68 ppm for Hg, respectively, while in Blongko, the heavy metal concentration was 0,03 ppm for Cd, 0.4 ppm for Pb, <1 ppm for Zn, and <0.05 ppm for Hg, respectively. The heavy metal concentration in H. opuntia of Totok Bay was 0.18 ppm for Cd, 2.2 ppm for Pb, 5.10 ppm for Zn, 0.74 ppm for Hg, while H. opuntia of Blongko contained 0.02 ppm of Cd, 0.2 ppm of lead, <0.5 ppm of Zn, and 0.009 ppm of Hg, respectively.Keywords : Cadmium (Cd); Lead (Pb); Zink (Zn); Mercury (Hg); Halimeda opuntia; Totok Bay; Blongko waters.ABSTRAKLogam berat dalam perairan dan sedimen meskipun memiliki kadar yang relatif rendah namun tidak akan mengalami degradasi bahkan dapat diabsorbsi dan terakumulasi secara biologis oleh alga laut. Tujuan penelitian adalah menganalisis kandungan logam berat dalam air laut, sedimen dan Halimeda opuntia di perairan Teluk Totok dan Perairan Blongko. Analisis sampel mengacu metode APHA, (2012) dan USEPA, (2005) yang dianalisis di Water Laboratory Nusantara (WLN). Hasil analisis konsentrasi logam berat dalam air laut di perairan Teluk Totok yaitu kadmium (Cd) <0,0001 ppm, timbal (Pb) <0,001 ppm, seng (Zn) <0,005 ppm dan merkuri (Hg) <0,00005 ppm sedangkan dari perairan Blongko yaitu konsentrasi kadmium (Cd) <0,0001 ppm, timbal (Pb) <0,001 ppm, seng (Zn) <0,005 ppm dan merkuri (Hg) <0,00005 ppm. Konsentrasi logam berat pada sedimen di perairan Teluk Totok yaitu kadmium (Cd) 4,71 ppm, timbal (Pb) 10,7 ppm, seng (Zn) 58 ppm dan merkuri (Hg) 2,68 ppm dan perairan Blongko dengan konsentrasi kadmium (Cd) 0,03 ppm, timbal (Pb) 0,4 ppm, seng (Zn) <1 ppm dan merkuri (Hg) <0,05 ppm. Sedangkan konsentrasi logam berat pada H. opuntia di perairan Teluk Totok dengan konsentrasi kadmium (Cd) 0,18 ppm, timbal (Pb) 2,2 ppm, seng (Zn) 5,10 ppm dan merkuri (Hg) 0,74 ppm dan perairan Blongko dengan konsentrasi kadmium (Cd) 0,02 ppm, timbal (Pb) 0,2, seng (Zn) <0,5 ppm dan merkuri (Hg) 0,009 ppm.Kata-kata kunci : Kadmium (Cd); Timbal (Pb); Seng (Zn); Merkuri (Hg); Halimeda opuntia; Teluk Totok; Perairan Blongko.